Early Childhood Islamic Boarding School in The Perspective of Education Sciences - Maesaroh Lubis; Darliana Sormin; Wael 'Ali Sayyed; Abdulroman Mahir (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This research is motivated by the fast growth of early childhood Islamic boarding schools (children of 5-7 years old). One of the reasons for the fast growth of Islamic boarding schools is the high public interest caused by the reduced trust of parents in modern educational institutions. This study used a qualitative literature review method with a systematic review approach. Data collection was carried out using an online reference search by entering the keyword "Early Childhood Islamic Boarding Schools" limited to articles published in the last ten years (2012-2022). The article is then processed to map themes that are often used by previous researchers. Then it is analyzed to get an overview of the focus aspects of the study of early childhood Islamic boarding schools in Indonesia. The results of the discussion show that research on the topic of Islamic boarding schools for early childhood has not been carried out much. However, there are quite a lot of studies on the impact of early childhood being away from their parents. The research results obtained concluded that the impact received by early childhood who lived and studied in Islamic boarding schools was the problem of attachment and parenting.